1996
DOI: 10.1149/1.1837028
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus Behavior of Metals and Oxides in Molten Carbonate under Oxidant and Reducing Atmospheres: I. Contact Angle and Electrolyte Displacement

Abstract: The wetting of metals and oxides by molten carbonate is an important factor affecting the performance of a molten carbonate fuel cell (MCFC). The distribution of the electrolyte among electrodes and matrix in the MCFC is dominated by the pore characteristics and wetting properties of these components. However, data on wetting, especially under load (current passage), are limited. In this study, the behavior of the meniscus at a metal is used to obtain information on wetting and electrochemical reactions. Menis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 6 publications
0
49
1
Order By: Relevance
“…The meniscus plays an important role in controlling the reaction rate. [8][9][10][11][12][13] Inaba et al reported that the hydrogen oxidation reaction (HOR) was affected by the shape of the meniscus, which determines the diffusion path of the dissolved gas.14 With an alkaline electrolyte, interesting interfacial phenomena have been observed. [15][16][17][18][19][20][21] In a previous study, we observed an in situ meniscus motion during the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a platinum electrode.…”
mentioning
confidence: 99%
“…The meniscus plays an important role in controlling the reaction rate. [8][9][10][11][12][13] Inaba et al reported that the hydrogen oxidation reaction (HOR) was affected by the shape of the meniscus, which determines the diffusion path of the dissolved gas.14 With an alkaline electrolyte, interesting interfacial phenomena have been observed. [15][16][17][18][19][20][21] In a previous study, we observed an in situ meniscus motion during the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a platinum electrode.…”
mentioning
confidence: 99%
“…This equation is derived from the condition of mechanical equilibrium between the interfacial tension (capillary) forces and the force associated with the hydrostatic pressure. This equation has been applied by Selman and co-workers [3,4,7] to analyse the meniscus height data at potentials very close to the equilibrium potential (open circuit potential, OCP), where nearequilibrium in the thermodynamic sense may be assumed.…”
Section: Resultsmentioning
confidence: 99%
“…Matsumura and Selman [3] used optical observation of the meniscus rise on vertical plate to study the effects of current passage and gas composition on wetting and spreading at a gold electrode. Mugikura and Selman [4] measured the contact angle values under oxidant and reducing atmospheres and used these results to estimate the change of electrolyte distribution in the MCFC under load. Suski et al [5,6] determined contact angles on Ni and NiO electrodes and compared the results with those on gold.…”
Section: Introductionmentioning
confidence: 99%
“…Also shown in Fig. 1 is the curve for the same melt we calculated from measurements of the wetting angle as a function of potential under the 3% H 2 + 40% ëé 2 + 57% N 2 atmosphere along the meniscus height at the vertical surface of the sample [6].…”
Section: Physical Chemistrymentioning
confidence: 99%